2007
DOI: 10.1194/jlr.m600495-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous reconstitution of discoidal HDL from sphingomyelin-containing model membranes by apolipoprotein A-I

Abstract: Nascent HDL is known to be formed by the interaction of apolipoprotein A-I (apoA-I) with transmembrane ABCA1, but the molecular mechanism by which nascent HDL forms is less well understood. Here, we studied how reconstituted high density lipoprotein (rHDL) forms spontaneously on the interaction of apoA-I with model membranes. The formation of rHDL from pure phosphatidylcholine (PC) large unilamellar vesicles (LUVs) proceeded very slowly at 37.0jC, but sphingomyelin (SM) -rich PC/SM LUVs, which are in a gel/liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 41 publications
(47 reference statements)
5
38
0
Order By: Relevance
“…5A). Consistent with the known membrane microsolubilizing activity of apoA-1 (26,27), a decrease in the light-scattering intensity was also observed for susceptible liposomes (Fig. 5A).…”
Section: Tlf Membrane Binding Is Facilitated By Low Ph and Mediated Bysupporting
confidence: 67%
See 1 more Smart Citation
“…5A). Consistent with the known membrane microsolubilizing activity of apoA-1 (26,27), a decrease in the light-scattering intensity was also observed for susceptible liposomes (Fig. 5A).…”
Section: Tlf Membrane Binding Is Facilitated By Low Ph and Mediated Bysupporting
confidence: 67%
“…We found that each of the protein components of TLF, Hpr, apoL-1, and indeed the HDL ubiquitous protein apoA-1 elicited the leakage of calcein from liposomes. The activity of apoA-1 was not unexpected as it is known to interact with cellular membranes with the concomitant formation of structures reminiscent of nascent HDL (26,27). Both of the unique protein components of TLF, apoL-1 and Hpr, efficiently permeabilized target liposomes.…”
Section: Discussionmentioning
confidence: 96%
“…An important question that has not been addressed is whether or not apo A-I can spontaneously solubilize more stable bilayers comprised of the phospholipids typically found in the plasma membrane of mammalian cells. In this case, no gel to liquid crystal phase transition to create lattice defects is apparent, although the presence of sphingomyelin, which creates a heterogeneous interface, can accelerate solubilization (56). The data in Fig.…”
Section: : Solubilization Of Exovesiculated Membrane Lipid Domains Bmentioning
confidence: 78%
“…The spontaneous solubilization is dependent on the cholesterol content and physical characteristics of the bilayer. 37 Typically, discoidal HDL particles contain two or three ApoA1 molecules. Larger particles include more protein.…”
Section: Apoa1 Structure and Function Hdl Particles And Apoa1mentioning
confidence: 99%